Cold atom–atom–ion three-body recombination of 4He–4He–X− (X = H or D). Issue 34 (16th August 2017) - Wang, Bin-Bin; Han, Yong-Chang; Gao, Wei; Cong, Shu-Lin
Abstract : The atom–atom–ion three-body recombination (TBR) of mixed 4 He and X − (X = H or D) systems is investigated by solving the Schrödinger equation using the adiabatic hyperspherical representation method. Abstract : The atom–atom–ion three-body recombination (TBR) of mixed 4 He and X − (X = H or D) systems is investigated by solving the Schrödinger equation using the adiabatic hyperspherical representation method. It is shown that the dominant products after a TBR in the ultracold limit ( E ≤ 0.1 mK × k B ) are different for the two systems. For the 4 He 4 HeH − system, the rate of TBR into the 4 HeH − ion is nearly two orders of magnitude larger than that of TBR into the neutral 4 He2 molecule. In contrast, the yield of 4 He2 is a little higher than that of 4 HeD − for the 4 He 4 HeD − system. Furthermore, since the adiabatic potentials become more attractive and the nonadiabatic couplings become much stronger by substituting D for H in the 4 He 4 HeH − system, the total TBR rate for the 4 He 4 HeD − system is nearly two orders of magnitude larger than that for the 4 He 4 HeH − system.